2013
DOI: 10.1002/pssc.201300347
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Si nanowires using Au catalyst accompanied with silicide nanoparticle formation

Abstract: Si nanowires were grown on Si(111) substrates, and the shape modification of the nanowires was demonstrated. With the Au catalyst, the highly symmetric faceted silicide solid particle in the Au‐Si eutectic solution was formed on the top of the nanowires, and the solid catalyst defined the shape of the Si nanowire. Namely, the VLS growth mechanism was followed by the VSS growth mechanism, and the modified shaped faceted Si nanowire was formed during the VSS growth. This result makes us to expect to control the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…In addition, it has been also shown that such a higher symmetric shaped silicide particles were only formed in the Au-Si solution, and defective irregular shaped Si nanowires were grown for the use of only MnCl 2 and Si sources without the Au catalyst. 17 The shape of the nanowires can be controlled according to the shape of the silicide catalyst at the top of the nanowire. Moreover, the shape of the grown silicide catalyst can be determined by the crystalline symmetry of the silicide phase nucleated in the Au-Si eutectic solution, its composition, crystalline structure, the surface energy of the grown crystal, and the growth environment, such as the growth temperature and the composition in the solution.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been also shown that such a higher symmetric shaped silicide particles were only formed in the Au-Si solution, and defective irregular shaped Si nanowires were grown for the use of only MnCl 2 and Si sources without the Au catalyst. 17 The shape of the nanowires can be controlled according to the shape of the silicide catalyst at the top of the nanowire. Moreover, the shape of the grown silicide catalyst can be determined by the crystalline symmetry of the silicide phase nucleated in the Au-Si eutectic solution, its composition, crystalline structure, the surface energy of the grown crystal, and the growth environment, such as the growth temperature and the composition in the solution.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, MnCl 2 , MnSi 1.7 , or other Mnbased compounds acted as catalyst for the growth of Si nanowires when the excess Si atoms were supplied. 10,49,50) It is interesting to compare the results with and without NH 4 Cl source for the nanosheets synthesized at 600 °C for 10 h (Samples 5 and 6). When NH 4 Cl was used as the source material, the dissociation of NH 4 Cl provided HCl formation, similar to the case of using deliquescent chloride; the HCl molecules were significantly transported to the CaSi 2 crystals at elevated temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…26) As already described, the nanostructure synthesis and the morphological and structural control of the Si and silicide nanowires using a chloride source material have been successfully demonstrated. 17,25,26) However, the transport phenomena of the source materials and the growth mechanism have not been clarified yet. The dependence of the distance from the source materials on the structural properties of the resulting nanowires was investigated in terms of the precursor flow rate, surface reactions, and the spatial distribution of the dissociation process of the precursors.…”
Section: Synthesis Of Crsi 2 Nanowires Using Crcl 2 As the Source Mat...mentioning
confidence: 99%
“…17) The synthesis of square Si nanowires and their growth evolution and structural properties are described elsewhere. 17,25) On the other hand, hexagonal Si nanowires are commonly obtained in the case of the 〈111〉 growth direction. 14) Actually, hexagonal Si nanowires with 〈111〉 directions were grown, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%